Emerging treatment options for ovarian cancer: focus on rucaparib - Mariappan L; Jiang XY; Jackson J; Drew Y (Dove Medical Press, 2017)
Lavanya Mariappan,1 Xue Yan Jiang,1 Josie Jackson,2 Yvette Drew2 1Northern Centre for Cancer Care, Freeman Hospital, 2Northern Institute for Cancer Research, Newcastle University, Newcastle-upon-Tyne, UK Abstract: Poly(ADP-ribose) polymerase (PARP) inhibitors (PARPi) are an exciting class of anticancer drugs, which have revolutionized the management of BRCA mutant/homologous recombination-deficient recurrent high-grade serous ovarian cancer (HGSOC). With three PARPi now approved by the US Food and Drug Administration, olaparib (Lynparza™), niraparib (Zejula™), and rucaparib (Rubraca™) in 2014 (and 2017 for the tablet formulation), 2016, and 2017, respectively, these drugs have now entered routine clinical practice. The marked single-agent efficacy of PARPi either as maintenance following response to platinum-based chemotherapy or as up-front treatment in these indications is based on the well-known concept of synthetic lethality. PARPi themselves work by blocking the repair of single-strand DNA breaks by the base excision/single-strand break repair pathway and can also be directly cytotoxic by the mechanism of PARP trapping. The greatest benefit in terms of progression-free survival, in all three PARPi maintenance registration studies, was seen in women with platinum-sensitive BRCA mutation-associated HGSOC. However, it is clear that non-BRCA HGSOC can benefit from PARPi and the ongoing challenge of biomarker driven studies is how best to define these patients. PARPi are well tolerated, but more information is needed to assess the longer-term/later onset toxicities as these agents are investigated in the first-line setting. The future direction and challenges for PARPi will be to continue to expand beyond BRCA and ovarian cancer by identifying molecular or functional signatures of response; to see if the durable responses in ovarian cancer can be improved and efficacy can be achieved in other cancer sub-types by combining with novel targeted agents. This review summarizes the development of PARPi as a class in ovarian cancer with particular focus on the PARPi rucaparib. Keywords: ovarian cancer, BRCA, PARP inhibitors, rucaparib